Aspergillus fumigatus secondary metabolite pyripyropene is important for the dual biofilm formation with Pseudomonas aeruginosa - Patricia Alves de Castro; Daniel Yuri Akiyama; Camila Figueiredo Pinzan; Thaila Fernanda dos Reis; Endrews Delbaje; Peter Rocha; Mario Augusto Izidoro; Sérgio Schenkman; Shinya Sugimoto; Norio Takeshita; Karin Steffen; Jessica L. Aycock; et al. (mBio)
ABSTRACT The human pathogenic fungus Aspergillus fumigatus establishes dual biofilm interactions in the lungs with the pathogenic bacterium Pseudomonas aeruginosa. Screening of 21 A. fumigatus null mutants revealed seven mutants (two G protein-coupled receptors, three mitogen-activated protein kinase receptors, a Gα protein, and one histidine kinase receptor) with reduced biofilm formation, specifically in the presence of P. aeruginosa. Transcriptional profiling and metabolomics analysis of secondary metabolites produced by one of these mutants, ΔgpaB (gpaB encodes a Gα protein), showed GpaB controls the production of several important metabolites for the dual biofilm interaction, including pyripyropene A, a potent inhibitor of mammalian acyl-CoA cholesterol acyltransferase. Deletion of pyr2, encoding a non-reducing polyketide synthase essential for pyripyropene biosynthesis, showed reduced A. fumigatus Δpyr2-P. aeruginosa biofilm growth, altered macrophage responses, and attenuated mouse virulence in a chemotherapeutic murine model. We identified pyripyropene as a novel player in the ecology and pathogenic interactions of this important human fungal pathogen.IMPORTANCEAspergillus fumigatus and Pseudomonas aeruginosa are two important human pathogens. Both organisms establish biofilm interactions in patients affected with chronic lung pulmonary infections, such as cystic fibrosis (CF) and chronic obstructive pulmonary disease. Colonization with A. fumigatus is associated with an increased risk of P. aeruginosa colonization in CF patients, and disease prognosis is poor when both pathogens are present. Here, we identified A. fumigatus genetic determinants important for the establishment of in vitro dual A. fumigatus-P. aeruginosa biofilm interactions. Among them, an A. fumigatus Gα protein GpaB is important for this interaction controlling the production of the secondary metabolite pyripyropene. We demonstrate that the lack of pyripyropene production decreases the dual biofilm interaction between the two species as well as the virulence of A. fumigatus in a chemotherapeutic murine model of aspergillosis. These results reveal a complete novel role for this secondary metabolite in the ecology and pathogenic interactions of this important human fungal pathogen.